1987
DOI: 10.1073/pnas.84.10.3365
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the CD2 antigen, the T-cell erythrocyte receptor, by a rapid immunoselection procedure.

Abstract: A cDNA encoding the CD2 antigen has been isolated by a highly efficient technique based on transient expression in COS cells and adherence of cells expressing surface antigen to antibody-coated dishes. COS cells expressing a CD2 cDNA isolated by this method readily formed rosettes with sheep as well as human and other mammalian erythrocytes. Pretreatment of transfected COS cells with anti-CD2 antibody, or pretreatment of human erythrocytes with anti-LFA-3 antibody, abolished rosette formation.The ability of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
395
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 842 publications
(396 citation statements)
references
References 36 publications
0
395
0
1
Order By: Relevance
“…We used this mAb as the basis for immunoselection of an FcaR cDNA clone, using a modification of the technique previously described by Seed and Aruffo (21). The U937 cell line represented a convenient source ofmRNA for cDNA library construction, since FcaR expression as measured by My43 binding is inducible by PMA treatment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used this mAb as the basis for immunoselection of an FcaR cDNA clone, using a modification of the technique previously described by Seed and Aruffo (21). The U937 cell line represented a convenient source ofmRNA for cDNA library construction, since FcaR expression as measured by My43 binding is inducible by PMA treatment .…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid DNA from the cDNA library was used to transfect a subconfluent layer ofmonkey COS-7 cells using DEAF dextran followed by chloroquine treatment, as described (20). FCaR`cells were selected by incubation in the My43 anti-FcciR mAb (14), followed by panning on anti-IgMcoated plates according to established procedures (21). Episomal DNA was prepared from the panned cells, amplified, and reintroduced into COS cells.…”
mentioning
confidence: 99%
“…Controls included a 2-kilobase Barn HI cDNA fragment of pactin, donated by Dr. Gary Nabel, and a full-length CD2 cDNA (31). Autoradiograms were exposed for 1, 5, or more hours.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular cloning revealed that NTBA is a member of the Ig superfamily characterized by structural features that allowed its assignment to the CD2 family. This family also includes CD2 [3] as well as CD48 [4], CD58 [5], CD84 [6], CD150 (signaling lymphocyte activation molecule, SLAM) [7], CD229 (hLy9) [8], CD244 (2B4) [9], CS1 (19A, CD2-like receptor activating cytotoxic cells, CRACC) [10][11][12], B lymphocyte activator macrophage-expressed (BLAME) [13], and CD84H1 [14]. These surface glycoproteins are characterized by similar structures consisting of a membrane distal IgV that lacks the typical disulfide bond, and a membrane proximal IgC2 domain, with the exception of CD229 that contains an IgV-IgC2 domains tandem repeat.…”
Section: Introductionmentioning
confidence: 99%